117: Association Between Fraction of Exhaled Nitrous Oxide (FeNO), Parameters of Asthma Control and Inhaled Corticosteroid Type in a Regional Paediatric Asthma Center. Issue 6 (1st June 2014) - Smith, RW; Downey, K; Snow, N; Dell, S; Smith, W
Abstract: BACKGROUND: FeNO is a known marker of airway inflammation, and is a topic of recent investigation for asthma control in children. OBJECTIVES: To investigate the relationship between FeNO and known parameters of asthma control in a regional paediatric asthma center. A secondary objective was to investigate the correlation between different types of inhaled corticosteroids (ICS) and FeNO concentration. DESIGN/METHODS: We conducted a retrospective chart review of children tested with both spirometry and FeNO over a one-year period. Collected data included age, anthropometrics, ICS type, equivalent dose, and duration of use, recent oral steroid use, asthma severity score, season, smoking status of family, and the presence or absence of; eczema, allergic rhinitis and respiratory tract infection. Data was analyzed by descriptive statistics and stepwise linear regression. A univariate generalized linear model was built to evaluate FeNO by ICS type, while correcting for statistically significant covariates. RESULTS: A total of 183 children were included. Mean (± SD) age was 12.8±2.8 years. Fluticasone was used most commonly (n=66, 36.1%) followed by ciclesonide (n=50 [27.3%]). Most children had moderate-persistent asthma (n=73 [39.9%]). FeNO level was associated with percent-change in FEV1 while adjusting for allergic rhinitis, parental smoking and ICS type (B=0.08 [95% CI 0.04 to 0.12]; P<0.001). Likewise, FeNO was associated with percent-change in FEF 25–75 while adjusting for parental smoking and ICS type (B=0.13 [95% CI 0.01 to 0.24]; P=0.03). However, FeNO accounted for only 16% and 9% of the variability in FEV1 and FEF 25–75, respectively. FeNO level differed by ICS type, while adjusting for equivalent dosing, allergic rhinitis and weight. Mean adjusted FeNO was lowest in fluticasone users compared to no ICS (mean difference ppb = 18.3 (95% CI 4.5 to 32.1]) and there was no difference in adjusted FeNO level between ciclesonide and no ICS (6.1 [95% CI −5.9 to 18.2]). CONCLUSIONS: FeNO levels correlate with known parameters of asthma control in a regional pediatric asthma center. However, FeNO accounts for only 16% and 9% of the variability in FEV1 and FeF 25–75. Mean adjusted FeNO varied by ICS type suggesting there is a difference in relative efficacy between inhaled corticosteroids beyond their dose equivalents.